Silicon-carbon negative electrode material, preparation method thereof, negative electrode sheet and lithium ion battery

CN117038904BActive Publication Date: 2026-10-09SICHUAN WUKE JINSI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311049047.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2026-10-09
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

[0007]本发明的第一目的在于提供一种硅碳负极材料,以解决现有硅基负极材料制得的电池容量低、循环性能差等问题

Benefits of technology

[0022](1) The silicon-carbon anode material provided by the present invention has a multilayer cage structure, which has high capacity, high first-efficiency and long cycle life. Specifically, by setting a pre-magnesium silicon suboxide core, the capacity and first-efficiency can be improved; by setting an expansion buffer carbon layer coated on the outer surface of the pre-magnesium silicon suboxide, lithium intercalation expansion space can be provided; by setting a hard carbon layer coated on silicon-carbon composite material and a deposited carbon layer coated on the outer surface of the hard carbon layer, excellent conductivity and lithium conductivity are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117038904B_ABST
    Figure CN117038904B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion batteries, in particular to a silicon-carbon negative electrode material, a preparation method thereof, a negative electrode sheet and a lithium ion battery. The silicon-carbon negative electrode material comprises a hard carbon layer, a deposited carbon layer coated on the outer surface of the hard carbon layer and a silicon-carbon composite material dispersed in the hard carbon layer; the silicon-carbon composite material comprises pre-magnesium silicon monoxide and an expansion buffer carbon layer coated on the surface of the pre-magnesium silicon monoxide; and the expansion buffer carbon layer contains conductive material. The silicon-carbon negative electrode material provided by the application has excellent rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a silicon-carbon anode material and its preparation method, an anode sheet, and a lithium-ion battery. Background Technology

[0002] Lithium-ion batteries are a typical example of a new type of green rechargeable battery system, and due to their excellent performance, they are widely used in many fields. The comprehensive performance of the negative electrode material in lithium-ion batteries is key to achieving long cycle life and high energy density.

[0003] Compared to traditional graphite anodes, silicon boasts an ultra-high theoretical specific capacity (4200 mAh / g) and a low delithiation potential (<0.5V). Driven by the demand for high-energy-density batteries in current portable consumer electronics and pure electric vehicles, high-capacity silicon materials have attracted widespread attention. However, silicon also has the following drawbacks as a lithium-ion battery anode material: Silicon is a semiconductor material with low conductivity. During electrochemical cycling, the insertion and extraction of lithium ions cause the material's volume to expand and contract by more than 300%. The resulting mechanical forces gradually pulverize the material, causing structural collapse and ultimately leading to the detachment of the electrode active material from the current collector, resulting in loss of electrical contact and a significant reduction in battery cycle performance. Furthermore, due to this volume effect, silicon struggles to form a stable solid electrolyte interphase (SEI) film in the electrolyte. With the destruction of the electrode structure, new SEI films continuously form on the exposed silicon surface, exacerbating silicon corrosion and capacity decay.

[0004] The lithium-ion insertion and extraction process involves the volume expansion and contraction of the silicon anode material, leading to silicon particle breakage, poor electrical contact, and instability of the SEI film. This ultimately causes problems such as reduced efficiency and rapid cycle capacity decay in the silicon anode material. x (0 < x < 2) The volume change of the negative electrode material during lithium-ion insertion / extraction is much smaller than that of the pure silicon negative electrode material, but its conductivity is slightly worse. Since carbon materials have certain mechanical strength and conductivity, the above problems are often solved by blending carbon and silicon oxide, but the effect is minimal.

[0005] Therefore, by designing carbon structures and SiO x To better improve the distribution of SiO x Improving the compressive strength of anode materials, addressing the volume expansion effect of silicon anode materials, and enhancing the conductivity of silicon anode material systems are of great significance for improving battery cycle performance.

[0006] In view of this, the present invention is hereby proposed. Summary of the Invention

[0007] The primary objective of this invention is to provide a silicon-carbon anode material to address the problems of low battery capacity and poor cycle performance in batteries made from existing silicon-based anode materials. The silicon-carbon anode material provided by this invention possesses advantages such as high capacity, high initial efficiency, rapid charge-discharge capability, and good cycle performance.

[0008] The second objective of this invention is to provide a method for preparing silicon-carbon anode materials.

[0009] The third objective of this invention is to provide a negative electrode sheet.

[0010] The fourth objective of this invention is to provide a lithium-ion battery.

[0011] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:

[0012] The present invention provides a silicon-carbon anode material, comprising a hard carbon layer, a deposited carbon layer covering the outer surface of the hard carbon layer, and a silicon-carbon composite material dispersed inside the hard carbon layer.

[0013] The silicon-carbon composite material includes pre-magnesium silicate and an expanded buffer carbon layer covering the surface of the pre-magnesium silicate.

[0014] The expanded buffer carbon layer contains conductive material.

[0015] This invention also provides a method for preparing silicon-carbon anode materials, comprising the following steps:

[0016] The pre-magnesium silicon suboxide, conductive material, binder and solvent are mixed and dried to obtain the first mixture.

[0017] The first mixture is mixed with the resin and the solvent and then cured to obtain the second mixture.

[0018] After carbonization, the second mixture undergoes chemical vapor deposition to form a deposited carbon layer, thereby obtaining the silicon-carbon anode material.

[0019] The present invention also provides a negative electrode sheet, which is mainly made of the aforementioned silicon-carbon negative electrode material.

[0020] The present invention also provides a lithium-ion battery, including the aforementioned negative electrode sheet.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] (1) The silicon-carbon anode material provided by the present invention has a multilayer cage structure, which has high capacity, high first-efficiency and long cycle life. Specifically, by setting a pre-magnesium silicon suboxide core, the capacity and first-efficiency can be improved; by setting an expansion buffer carbon layer coated on the outer surface of the pre-magnesium silicon suboxide, lithium intercalation expansion space can be provided; by setting a hard carbon layer coated on silicon-carbon composite material and a deposited carbon layer coated on the outer surface of the hard carbon layer, excellent conductivity and lithium conductivity are achieved.

[0023] (2) The method for preparing silicon-carbon anode material provided by the present invention can improve the capacity and initial coulombic efficiency of silicon-carbon anode material, improve fast charge and fast discharge performance, and improve the cycle performance of silicon-carbon anode material.

[0024] (3) The method for preparing silicon-carbon anode material provided by the present invention also has the advantages of simple operation, short process and low cost. Attached Figure Description

[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0026] Figure 1 This is a schematic cross-sectional view of the silicon-carbon anode material provided by the present invention. Detailed Implementation

[0027] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0028] In a first aspect, the present invention provides a silicon-carbon anode material for lithium-ion batteries, which has a multilayer cage structure, see [reference needed]. Figure 1 The diagram shown is a cross-sectional view of the silicon-carbon anode material, which includes a hard carbon layer, which is mainly made of resin through carbonization.

[0029] The silicon-carbon anode material also includes a deposited carbon layer covering the outer surface of the hard carbon layer. The deposited carbon layer is mainly prepared by chemical vapor deposition (CVD) of carbon source.

[0030] The silicon-carbon anode material also includes silicon-carbon composite materials dispersed within the hard carbon layer. It can be understood that several silicon-carbon composite material particles are distributed within the hard carbon layer; that is, the hard carbon layer coats several silicon-carbon composite material particles and interconnects these particles.

[0031] The silicon-carbon composite material comprises pre-magnesium silicate and an expansion buffer carbon layer coating the surface of the pre-magnesium silicate. It is understood that the pre-magnesium silicate is coated with the expansion buffer carbon layer, which in turn is coated with a hard carbon layer.

[0032] The expansion buffer carbon layer is mainly composed of hard carbon, and also contains conductive materials.

[0033] The silicon-carbon anode material provided by this invention can improve capacity and first-time efficiency by setting a pre-magnesium silicon suboxide core; it can provide lithium intercalation expansion space by setting an expansion buffer carbon layer covering the outer surface of the pre-magnesium silicon suboxide; and it has excellent electrical conductivity and lithium conductivity by setting a hard carbon layer covering silicon-carbon composite material and a deposited carbon layer covering the outer surface of the hard carbon layer.

[0034] Preferably, the conductive material includes at least one of carbon nanotubes, graphene, fumed carbon fibers, conductive carbon black, and acetylene black.

[0035] More preferably, the conductive carbon black includes SP conductive carbon black.

[0036] Figure 1 The illustration shows a case where carbon nanotubes and graphene are used as conductive materials. However, it is understood that in this application, carbon nanotubes can be used alone as conductive materials, or graphene or other conductive materials can be used alone, or more than two conductive materials can be used simultaneously.

[0037] This invention improves the conductivity of silicon-carbon anode materials by incorporating a conductive material within the expansion buffer carbon layer. It is understood that the hard carbon forming the expansion buffer carbon layer is not dense hard carbon; therefore, incorporating a conductive material within the expansion buffer carbon layer enhances its conductivity and lithium conductivity.

[0038] Preferably, the D50 particle size of the pre-magnesium silicon suboxide is 30-800 nm; including but not limited to point values ​​or ranges between any one of 30 nm, 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, and 800 nm.

[0039] Pre-magnesium silicon suboxide with the above-mentioned particle size range has a lower manufacturing cost and less lithium intercalation expansion, thus balancing cost and performance.

[0040] Preferably, the pre-magnesium silicon suboxide is mainly obtained by pre-magnesium treatment of silicon suboxide, wherein the chemical formula of the silicon suboxide is SiO. x Where 1 ≥ x > 0; the values ​​of x include, but are not limited to, any point value or a range between any two of the following: 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0. It is understandable that the value of x remains unchanged before and after pre-magnesium treatment.

[0041] Using x values ​​within the above range results in a high silicon content, thus producing a negative electrode material with a higher specific capacity.

[0042] In a preferred embodiment, the method for preparing pre-magnesium silicon suboxide includes the following steps: mixing silicon suboxide and magnesium powder at a mass ratio of 6 to 10:1 until homogeneous, then calcining at 600 to 900°C for 2 to 6 hours under an inert atmosphere, and obtaining pre-magnesium silicon suboxide after cooling. More preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0043] Compared with silicon suboxide, pre-magnesium silicon suboxide has advantages such as higher initial efficiency and better cycle performance.

[0044] Preferably, the mass of the pre-magnesium silicon suboxide accounts for 60% to 95% of the total mass of the silicon-carbon anode material, including but not limited to any one of 60%, 65%, 70%, 75%, 80%, 85%, 90%, and 95%, or any range between two of them.

[0045] When the mass ratio of pre-magnesium silicate is within the above range, both high capacity and high cycle performance can be achieved.

[0046] Preferably, the average particle size (i.e., D50 particle size) of the silicon-carbon anode material is 6 to 10 μm, including but not limited to the point value of any one of 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm or the range between any two.

[0047] In a preferred embodiment, the thickness of the deposited carbon layer is 5–50 nm, including but not limited to a point value or a range between any two of 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, and 45 nm. It is understood that the thickness of the deposited carbon layer is related to the chemical vapor deposition time.

[0048] By using the above-mentioned deposition thickness, both coating can be achieved well, and the cycle performance of the anode material can be enhanced.

[0049] Secondly, the present invention provides a method for preparing the silicon-carbon anode material, comprising the following steps:

[0050] Pre-magnesium silicate, conductive material, binder, and solvent are mixed and dried to obtain a first mixture. In the first mixture, the binder containing conductive material coats the surface of the pre-magnesium silicate, which, after subsequent carbonization, forms a silicon-carbon composite material.

[0051] The first mixture is mixed with the resin and the solvent and then cured to obtain the second mixture. After mixing, the resin coats the outer surface of the first mixture and binds the particles of the first mixture together. After subsequent carbonization, the resin forms a hard carbon layer.

[0052] After carbonization, the second mixture undergoes chemical vapor deposition to form a deposited carbon layer, thus obtaining the silicon-carbon anode material. During the chemical vapor deposition process, the deposited carbon layer forms on the surface of the hard carbon layer and completes the coating.

[0053] The method for preparing silicon-carbon anode material provided by this invention employs a pre-magnesium oxide sub-silicon core, which can improve the capacity and initial coulombic efficiency of the silicon-carbon anode material. The addition of conductive materials improves conductivity. After the binder is carbonized, an expansion buffer carbon layer is formed, which provides space for lithium intercalation expansion, improves the cycle performance of the silicon-carbon anode material, and avoids silicon corrosion and capacity decay. After the resin is carbonized, a hard carbon layer is formed, and a deposited carbon layer is formed by chemical vapor deposition, which improves conductivity and lithium conduction efficiency, and improves the fast charging and discharging performance of lithium batteries.

[0054] Furthermore, the hard carbon layer has a certain mechanical strength, which can improve the compressive strength of silicon-carbon anode materials, maintain the integrity of materials during the compaction of battery electrodes, and thus improve the cycle performance of the battery.

[0055] In addition, the above preparation method has the advantages of simple operation, short process, low cost and suitability for mass production.

[0056] In a preferred embodiment, the conductive material includes at least one of carbon nanotubes, graphene, fumed carbon fibers, conductive carbon black, and acetylene black.

[0057] More preferably, the carbon nanotubes include one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes. The diameter of the carbon nanotubes is 1 to 2 nm.

[0058] More preferably, the graphene comprises multilayer graphene. The thickness of the graphene is 0.5–1.2 nm, and the diameter is 0.5–3 μm.

[0059] Multilayer graphene is inexpensive and can reduce the production cost of anode materials.

[0060] Preferably, the mass ratio of the pre-magnesium silicon suboxide, the conductive material, and the binder is 40-100 (also 50, 60, 70, 80, or 90): 0.1-10 (also 0.5, 1, 2, 3, 4, 5, 6, 7, 8, or 9): 5-25 (also 8, 10, 15, 20, or 23).

[0061] In a preferred embodiment, during the mixing process of the pre-magnesium silicate, conductive material, binder and solvent, the mass ratio of pre-magnesium silicate to solvent is 40-100:80-200, wherein 80-200 can also be selected as 90, 100, 120, 140, 150, 170 or 190.

[0062] In a preferred embodiment, during the mixing process of the pre-magnesium silicon suboxide, conductive material, binder, and solvent, the mixing time is 0.5 to 5 hours, including but not limited to any one of 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours, or a range between any two. More preferably, the mixing process is carried out at a stirring speed of 100 to 500 rpm, wherein the stirring speed includes but is not limited to any one of 100 rpm, 200 rpm, 300 rpm, 400 rpm, and 500 rpm, or a range between any two.

[0063] In a preferred embodiment, during the drying process after the pre-magnesium silicon suboxide, conductive material, binder, and solvent are mixed, the drying temperature is 100–160°C, including but not limited to any one of 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, and 160°C, or any range between any two; the holding time is 30–120 min, including but not limited to any one of 30 min, 40 min, 50 min, 60 min, 80 min, 90 min, 100 min, and 120 min, or any range between any two.

[0064] In a preferred embodiment, the drying process after mixing the pre-magnesium silicate, conductive material, binder, and solvent further includes a pulverization step after drying. More preferably, the pulverization is performed until the average particle size of the first mixture is 2 to 6 μm, including but not limited to point values ​​of any one of 2 μm, 3 μm, 4 μm, 5 μm, and 6 μm, or a range between any two.

[0065] Preferably, the mass ratio of the first mixture to the resin is 5-10 (or 6, 7, 8 or 9): 4-8 (or 5, 6 or 7).

[0066] In a preferred embodiment, during the process of mixing the first mixture with the resin and the solvent, the mass ratio of the first mixture to the solvent is 5-10:5-15, wherein 5-15 can also be selected as 7, 9, 10, 12 or 14.

[0067] In a preferred embodiment, during the process of mixing the first mixture with the resin and the solvent, the solvent used is any conventional organic solvent, such as methanol, ethanol, ethylene glycol, etc., but not limited thereto.

[0068] In a preferred embodiment, during the curing process after the first mixture is mixed with the resin and the solvent, the curing temperature is 100-180°C, including but not limited to any one of 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, and 170°C, or any range between two of them.

[0069] In a preferred embodiment, the curing process after mixing the first mixture with the resin and the solvent includes a pulverization step after curing. More preferably, the second mixture is pulverized to an average particle size of 3-7 μm, including but not limited to point values ​​of any one of 3 μm, 4 μm, 5 μm, 6 μm, and 7 μm, or a range between any two.

[0070] Preferably, the binder comprises at least one of asphalt, starch, glucose, and methyl methacrylate.

[0071] It is understandable that the aforementioned adhesive serves both as a binder and as a carbon source to form an expansion buffer carbon layer.

[0072] In a preferred embodiment, during the drying process following the mixing of the pre-magnesium silicate, conductive material, binder, and solvent, the solvent used includes water and / or an organic solvent. More preferably, the organic solvent includes at least one selected from ethanol, methanol, ethylene glycol, acetone, toluene, ethyl acetate, and butyl acetate.

[0073] Understandably, when starch or glucose is used as the binder, water can be used as the solvent; when asphalt or methyl methacrylate is used as the binder, an organic solvent can be used.

[0074] Preferably, the resin comprises a thermosetting resin.

[0075] Using thermosetting resins results in a high carbon yield, and the resulting hard carbon layer contains a large number of micropores, which can further provide buffer space for silicon expansion.

[0076] More preferably, the thermosetting resin includes at least one of phenolic resin, epoxy resin, polyester resin, bismaleimide resin, polyimide resin and cyanate ester resin.

[0077] Polyester resins include saturated polyester resins and unsaturated polyester resins. Unsaturated polyester resins include, for example, vinyl resins (also known as epoxy acrylic resins) and halogenated unsaturated polyesters, but are not limited to these.

[0078] Preferably, the carbonization temperature is 750–1000°C, including but not limited to any one of 800°C, 850°C, 900°C, and 950°C, or a range between any two; the carbonization time is 30–300 min, including but not limited to any one of 60 min, 90 min, 120 min, 150 min, 180 min, 210 min, 240 min, and 270 min, or a range between any two.

[0079] Preferably, the carbon source used in the chemical vapor deposition includes at least one selected from methane, methanol, ethane, ethylene, acetylene, propane, propylene, butane, and toluene.

[0080] Preferably, the temperature of the chemical vapor deposition is 750 to 1000°C, including but not limited to any one of 800°C, 850°C, 900°C, and 950°C, or any range between two of them.

[0081] Preferably, the chemical vapor deposition time is 120 to 1200 min, including but not limited to any one of 150 min, 180 min, 210 min, 240 min, 270 min, 300 min, 360 min, 420 min, 500 min, 800 min, and 1000 min, or any range between two of them.

[0082] By using the above-mentioned chemical vapor deposition time, a carbon layer with a thickness of 5–50 nm can be obtained, thereby improving the cycle performance of silicon-carbon anode materials.

[0083] Thirdly, the present invention provides a negative electrode sheet, which is mainly made of the aforementioned silicon-carbon negative electrode material, for example, by coating the silicon-carbon negative electrode material onto a current collector.

[0084] In a preferred embodiment, the raw materials for preparing the negative electrode sheet further include at least one of a conductive agent, a binder, a solvent, and a thickener.

[0085] Fourthly, the present invention provides a lithium-ion battery, including the aforementioned negative electrode sheet.

[0086] Understandably, lithium-ion batteries also include a positive electrode, a separator, and an electrolyte.

[0087] The lithium-ion battery provided by this invention has both excellent rate performance and cycle performance.

[0088] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0089] Example 1

[0090] The method for preparing pre-magnesium silicon suboxide used in this embodiment includes the following steps: preparing silicon suboxide (SiO2) x The mixture of magnesium powder and x (where x = 0.9) was homogeneous at a mass ratio of 8:1, and then calcined at 800℃ for 4 hours under a nitrogen atmosphere. After cooling, pre-magnesium silicate with a D50 particle size of 400nm was obtained.

[0091] The method for preparing silicon-carbon anode material provided in this embodiment includes the following steps:

[0092] (1) Mix 40 parts of pre-magnesium silicate, 1 part of single-walled carbon nanotubes, 5 parts of glucose and 80 parts of water and stir evenly for 1 hour at a stirring speed of 300 rpm to obtain a mixture. Heat the mixture to 160°C within 90 minutes and keep it at that temperature for 30 minutes to dry it, so that the water can be fully evaporated. Then, pulverize it to obtain a first mixture with an average particle size of 3 μm.

[0093] (2) Take 10 parts of the first mixture obtained in step (1), mix it with 8 parts of 2130 phenolic resin and 15 parts of methanol, stir it evenly and then cure it at 180°C. After curing, crush it to obtain the second mixture with an average particle size of 6μm.

[0094] (3) The second mixture obtained in step (2) is carbonized at 800°C for 60 minutes, and then chemical vapor deposition is performed at 800°C using methane as the carbon source to form a carbon layer. The chemical vapor deposition time is 120 minutes, and silicon-carbon anode material is obtained.

[0095] The silicon-carbon anode material prepared in this embodiment includes a hard carbon layer, a deposited carbon layer coating the outer surface of the hard carbon layer, and a silicon-carbon composite material dispersed inside the hard carbon layer. The silicon-carbon composite material includes pre-magnesium silicate and an expansion buffer carbon layer coating the surface of the pre-magnesium silicate; the expansion buffer carbon layer contains single-walled carbon nanotubes. The average particle size of the silicon-carbon anode material prepared in this embodiment is 6 μm. The pre-magnesium silicate accounts for 60% of the total mass of the silicon-carbon anode material (measured using a carbon-sulfur analyzer; 0.15 g of silicon-carbon anode material mixed with flux is placed in the instrument for testing; the same applies to the following embodiments).

[0096] Example 2

[0097] The method for preparing pre-magnesium silicon suboxide used in this embodiment includes the following steps: preparing silicon suboxide (SiO2) x (where x = 0.5) and magnesium powder are mixed evenly at a mass ratio of 6:1, and then calcined at 900℃ for 2 hours under a nitrogen atmosphere. After cooling, pre-magnesium silicate with a D50 particle size of 50nm is obtained.

[0098] The method for preparing the silicon-carbon anode material provided in this embodiment includes the following steps:

[0099] (1) Mix 70 parts of pre-magnesium silicate, 3 parts of multilayer graphene, 10 parts of starch and 100 parts of water and stir evenly for 3 hours at a stirring speed of 500 rpm to obtain a mixture. Heat the mixture to 130°C within 90 minutes and keep it at that temperature for 60 minutes to dry it, so that the water can be fully evaporated. Then, pulverize it to obtain a first mixture with an average particle size of 4 μm.

[0100] (2) Take 5 parts of the first mixture obtained in step (1), mix it with 4 parts of 2130 phenolic resin and 5 parts of ethylene glycol, stir evenly and then cure at 150°C. After curing, crush it to obtain the second mixture with an average particle size of 7μm.

[0101] (3) The second mixture obtained in step (2) is carbonized at 900°C for 120 min, and then chemical vapor deposition is performed at 900°C using methanol as the carbon source to form a carbon layer. The chemical vapor deposition time is 300 min, and silicon-carbon anode material is obtained.

[0102] The silicon-carbon anode material prepared in this embodiment includes a hard carbon layer, a deposited carbon layer coating the outer surface of the hard carbon layer, and a silicon-carbon composite material dispersed within the hard carbon layer. The silicon-carbon composite material includes pre-magnesium silicon suboxide and an expansion buffer carbon layer coating the surface of the pre-magnesium silicon suboxide; the expansion buffer carbon layer contains multiple layers of graphene. The average particle size of the silicon-carbon anode material prepared in this embodiment is 7 μm. The pre-magnesium silicon suboxide accounts for 65% of the total mass of the silicon-carbon anode material.

[0103] Example 3

[0104] The method for preparing pre-magnesium silicon suboxide used in this embodiment includes the following steps: preparing silicon suboxide (SiO2) x (where x = 1) and magnesium powder are mixed evenly at a mass ratio of 10:1, and then calcined at 600℃ for 6 hours under a nitrogen atmosphere. After cooling, pre-magnesium silicate with a D50 particle size of 700nm is obtained.

[0105] The method for preparing the silicon-carbon anode material provided in this embodiment includes the following steps:

[0106] (1) Mix 100 parts of pre-magnesium silicate, 5 parts of multi-walled carbon nanotubes, 3 parts of multilayer graphene, 25 parts of asphalt, and 180 parts of acetone and stir evenly for 5 hours at a stirring speed of 200 rpm to obtain a mixture. Heat the mixture to 100°C within 90 minutes and keep it at that temperature for 120 minutes to dry it, allowing the acetone to fully evaporate. Then, pulverize the mixture to obtain a first mixture with an average particle size of 5 μm.

[0107] (2) Take 8 parts of the first mixture obtained in step (1), mix it with 6 parts of 901 vinyl ester resin and 10 parts of ethanol, stir it evenly and then cure it at 120°C. After curing, crush it to obtain a second mixture with an average particle size of 8μm.

[0108] (3) The second mixture obtained in step (2) is carbonized at 1000℃ for 30 min, and then chemical vapor deposition is performed at 1000℃ using ethylene as the carbon source to form a carbon layer. The chemical vapor deposition time is 240 min, and silicon-carbon anode material is obtained.

[0109] The silicon-carbon anode material prepared in this embodiment includes a hard carbon layer, a deposited carbon layer coating the outer surface of the hard carbon layer, and a silicon-carbon composite material dispersed within the hard carbon layer. The silicon-carbon composite material includes pre-magnesium silicon suboxide and an expanded buffer carbon layer coating the surface of the pre-magnesium silicon suboxide; the expanded buffer carbon layer contains multi-walled carbon nanotubes and multilayer graphene. The average particle size of the silicon-carbon anode material prepared in this embodiment is 8 μm. The pre-magnesium silicon suboxide accounts for 75% of the total mass of the silicon-carbon anode material.

[0110] Example 4

[0111] The preparation method of the silicon-carbon anode material provided in this embodiment is basically the same as that in embodiment 3, except that: in step (1), the mass fraction of asphalt is replaced with 5 parts, and in step (2), the mass fraction of the first mixture is replaced with 10 parts, and the mass fraction of epoxy acrylic resin is replaced with 4 parts.

[0112] In this embodiment, the mass of pre-magnesium silicon suboxide accounts for 84% of the total mass of the silicon-carbon anode material.

[0113] Example 5

[0114] The preparation method of silicon-carbon anode material provided in this embodiment is basically the same as that in embodiment 3, except that in step (3), the chemical vapor deposition time is replaced with 600 min.

[0115] Comparative Example 1

[0116] The preparation method of the silicon-carbon anode material provided in this comparative example is basically the same as that in Example 1. The only difference is that chemical vapor deposition was not performed in step (3), that is, no carbon layer was deposited in the silicon-carbon anode material prepared in this comparative example.

[0117] Comparative Example 2

[0118] The preparation method of the silicon-carbon anode material provided in this comparative example is basically the same as that in Example 1. The only difference is that single-walled carbon nanotubes were not added in step (1), that is, the expansion buffer carbon layer of the silicon-carbon anode material prepared in this comparative example does not contain conductive materials.

[0119] Comparative Example 3

[0120] The preparation method of the silicon-carbon anode material provided in this comparative example is basically the same as that in Example 1, except that the pre-magnesium silicon suboxide in step (1) is replaced with untreated silicon suboxide (SiO2). x , where x = 0.85.

[0121] Comparative Example 4

[0122] The preparation method of the silicon-carbon anode material provided in this comparative example includes the following steps:

[0123] (1) Mix 100 parts of pre-magnesium silicate, 5 parts of multi-walled carbon nanotubes, 3 parts of multilayer graphene and 180 parts of acetone and stir evenly. The mixing time is 5 hours and the stirring speed is 200 rpm to obtain a mixture. Heat the mixture to 100℃ within 90 minutes and keep it at that temperature for 120 minutes to dry it, so that the acetone can be fully volatilized, to obtain the first mixture.

[0124] (2) Same as step (2) in Example 3.

[0125] (3) Same as step (3) in Example 3.

[0126] The silicon-carbon anode material prepared in this comparative example has no expansion buffer carbon layer, and the hard carbon layer directly coats the pre-magnesium silicon suboxide particles.

[0127] Experimental Example

[0128] The silicon-carbon anode materials prepared in the above embodiments and comparative examples were used to make lithium-ion batteries, and the electrochemical performance of each battery was tested. The test results are shown in Table 1.

[0129] The battery preparation and testing methods are as follows:

[0130] (1) Prepare a slurry by mixing the silicon-carbon anode material, SP, CNT, CMC and SBR prepared above in a mass ratio of 75:12:3:5:5. Coat the slurry on an 8μm copper foil and dry it in a forced-air oven at 60℃ for 2h. Then cut several Ф12mm electrode sheets, pack them into a vacuum oven at 110℃ and dry them for 7h.

[0131] (2) After baking is completed, quickly transfer the battery to the glove box, use a Ф14mm lithium metal sheet as the counter electrode, use a single-sided ceramic diaphragm, and use 1mol / L LiPF6 / (EC+DMC) (volume ratio 1:1) with 3% VC and 3% FEC as the electrolyte. Assemble the button battery in the glove box, and control the water and oxygen content in the glove box to below 0.1ppm.

[0132] (3) Perform charge-discharge cycle tests on each assembled battery. The charge-discharge test equipment is the LAND battery test system (from Wuhan Lanhe Electronics Co., Ltd.). The test conditions are: room temperature, discharge to 5mV in 0.1C and 0.02C steps for the first three weeks, charge to 1.5V at 0.1C constant current, and then cycle 200 times at 5C / 5C after the fourth week.

[0133] Table 1 Performance test results of each battery

[0134] Example 1 1352 89.9 98.4 Example 2 1387 88.7 98.1 Example 3 1421 88.9 97.7 Example 4 1503 88.5 96.9 Example 5 1403 90.1 98.2 Comparative Example 1 1355 86.3 73.2 Comparative Example 2 1335 89.5 78.3 Comparative Example 3 1265 79.1 71.1 Comparative Example 4 1396 88.5 72.5

[0135] As can be seen from Table 1, the silicon-carbon anode materials prepared in each embodiment have higher capacity and first-time efficiency, and better cycle performance.

[0136] Comparative Example 1 showed a decrease in cycle performance due to the absence of a deposited carbon layer; Comparative Example 2 showed a decrease in capacity and fast-charge cycle performance due to the lack of added carbon nanotubes; Comparative Example 3 showed a decrease in first-efficiency and cycle performance due to the use of untreated silicon suboxide instead of the pre-magnesium silicon suboxide in Example 1; and Comparative Example 4 showed a decrease in cycle performance due to the absence of an expansion buffer carbon layer.

[0137] Therefore, the silicon-carbon anode material provided by the present invention has the advantages of high capacity, high initial efficiency and long cycle life by adopting a specific multi-layered cage structure.

[0138] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.

Claims

1. A silicon-carbon anode material, characterized in that, It includes a hard carbon layer, a deposited carbon layer covering the outer surface of the hard carbon layer, and a silicon-carbon composite material dispersed inside the hard carbon layer. The silicon-carbon composite material includes pre-magnesium silicate and an expanded buffer carbon layer covering the surface of the pre-magnesium silicate. The expanded buffer carbon layer contains a conductive material; The preparation method of the silicon-carbon anode material includes the following steps: The pre-magnesium silicon suboxide, conductive material, binder and solvent are mixed and dried to obtain the first mixture. The first mixture is mixed with the resin and the solvent and then cured to obtain the second mixture. After carbonization, the second mixture undergoes chemical vapor deposition to form a deposited carbon layer, thereby obtaining the silicon-carbon anode material; The hard carbon layer is formed by carbonization of resin; The expansion buffer carbon layer is formed by carbonizing the binder.

2. The silicon-carbon anode material according to claim 1, characterized in that, The conductive material includes at least one of carbon nanotubes, graphene, fumed carbon fibers, conductive carbon black, and acetylene black.

3. The silicon-carbon anode material according to claim 1, characterized in that, The D50 particle size of the pre-magnesium silicate is 30~800nm.

4. The silicon-carbon anode material according to claim 1, characterized in that, The pre-magnesium silicon suboxide is mainly obtained by pre-magnesium treatment of silicon suboxide, wherein the chemical formula of the silicon suboxide is SiO. x , where 1≥x>0.

5. The silicon-carbon anode material according to claim 1, characterized in that, The pre-magnesium silicon suboxide accounts for 60% to 95% of the total mass of the silicon-carbon anode material.

6. The silicon-carbon anode material according to claim 1, characterized in that, The average particle size of the silicon-carbon anode material is 6~10μm.

7. The silicon-carbon anode material according to claim 1, characterized in that, The mass ratio of the pre-magnesium silicate, the conductive material, and the binder is 40~100:0.1~10:5~25.

8. The silicon-carbon anode material according to claim 1, characterized in that, The mass ratio of the first mixture to the resin is 5~10:4~8.

9. The silicon-carbon anode material according to claim 1, characterized in that, The binder includes at least one of asphalt, starch, glucose, and methyl methacrylate.

10. The silicon-carbon anode material according to claim 1, characterized in that, The resin includes thermosetting resins.

11. The silicon-carbon anode material according to claim 10, characterized in that, The thermosetting resin includes at least one of phenolic resin, epoxy resin, polyester resin, bismaleimide resin, polyimide resin, and cyanate ester resin.

12. The silicon-carbon anode material according to claim 1, characterized in that, The carbonization temperature is 750~1000℃, and the carbonization time is 30~300min.

13. The silicon-carbon anode material according to claim 1, characterized in that, The carbon source used in the chemical vapor deposition includes at least one of methane, methanol, ethane, ethylene, acetylene, propane, propylene, butane, and toluene.

14. The silicon-carbon anode material according to claim 1, characterized in that, The temperature of the chemical vapor deposition is 750~1000℃, and the time of the chemical vapor deposition is 120~1200min.

15. A negative electrode sheet, characterized in that, It is mainly made of silicon-carbon anode material as described in any one of claims 1 to 14.

16. A lithium-ion battery, characterized in that, Includes the negative electrode sheet as described in claim 15.

Citation Information

Patent Citations

  • Negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

    CN116093287A

  • Silicon-based negative electrode material, preparation method thereof and lithium ion battery

    CN116487552A